1969
DOI: 10.2135/cropsci1969.0011183x000900060075x
|View full text |Cite
|
Sign up to set email alerts
|

Registration of C.P. 57‐603 Sugarcane1 (Reg. No. 9)

Abstract: Department of Agriculture and the Florida Agricultural Experiment Stations and was released to the industry in 1957.C.P. 50-28 is an early-maturing, medium-barrel, early-flowering cultivar. It is adapted to the cold organic and sandy soils of Florida because ot~ its outstanding stubbling or ratooning ability. Although the fiber content of C.P. 50-28 is objectionable to some processors, the cold tolerance and exceptional stubbling qualities are distinct advantages of this cultivar.Seedcane of C.P. 50-28 wil be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The most successful commercial parent was CP 68-1067 [ 24 ], which was used as a parent six times from which new cultivars were selected. The female and male parents of CP 68-1067 are CP 52-68 [ 20 ] and CP 57-603 [ 25 ], respectively, and they were also cultivars. Cultivar progeny of CP 68-1067 are CP 75-1082 [ 26 ], CP 75-1632 [ 27 ], CP 77-1776 [ 28 ], CP 78-1628 [ 29 ], CP 80-1743 [ 30 ], and CP 81-1384 [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most successful commercial parent was CP 68-1067 [ 24 ], which was used as a parent six times from which new cultivars were selected. The female and male parents of CP 68-1067 are CP 52-68 [ 20 ] and CP 57-603 [ 25 ], respectively, and they were also cultivars. Cultivar progeny of CP 68-1067 are CP 75-1082 [ 26 ], CP 75-1632 [ 27 ], CP 77-1776 [ 28 ], CP 78-1628 [ 29 ], CP 80-1743 [ 30 ], and CP 81-1384 [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Field trials planted with smut‐inoculated stalks were conducted in 2014–2015. CP 10‐1620 had an average of 0.2 plants with sori compared with a mean of 11.3% plants with sori for CP 57‐0603 (Dunckchnan et al., 1969) and 11.4% plants with sori for CP 78‐1628. No natural stools of smut were found in the plot observations on CP 10‐1620 grown in sand soils.…”
Section: Characteristicsmentioning
confidence: 99%
“…Flynn et al (2005) suggested that losses in sucrose yield due to SCYLV ranged from −3.4% to 8.0% in Florida. Susceptibility of CP 10-1620 to SCYLV was compared to CP 57-603 (Dunckchnan et al, 1969) and CP 78-1628 because of their susceptibility to SCYLV. Susceptibility of CP 10-1620 to smut was compared to CP 78-1628 because of its susceptibility to smut.…”
Section: Disease Resistancementioning
confidence: 99%
“…Cultivar CP 70‐1133 was widely used on sand soils in Florida before it became susceptible to brown rust. Also, ‘CP 57‐603’ (Dunckelman et al, 1969), which was a minor cultivar in Florida but widely planted in Colombia and also used in other countries, is a great‐great‐great grandparent of CP 00‐1446.…”
mentioning
confidence: 99%